The Effect of Muslim Religiosity and Innovation Capability on Firm Survival: A Study on Small Enterprises During the Covid-19 Pandemic - Utomo, Humam Santosa (Ekonomi Syariah IAIN Kudus, 2020)
This research aimed to examine and analyze the effect of Muslim religiosity and innovation capability on firm survival. Also, this research investigated the moderation role of environmental uncertainty on the effect of Muslim religiosity and innovation capability on firm survival. The study was conducted during the covid-19 pandemic. The analysis unit of this research was the owners of processed food small enterprises fostered by the regional government of Bantul Regency, Yogyakarta. The number of respondents involved in this research was 120 Muslim entrepreneurs. Data were collected using closed questionnaires distributed online, than processed using SEM-WarpPLS. The results showed that the Muslim religiosity and innovation capability significantly affected firm survival. Environmental uncertainty significantly weakened the effect of innovation capability on firm survival. However, environmental uncertainty insignificantly weakened the effect of Muslim religiosity on firm survival. These research results indicate the importance of religious formation for small entrepreneurs in this crisis time. Innovation is also important in increasing the firm survival of small companies during the covid-19 pandemic.